Toward A Greater Understanding of the Ways Family-Based Treatment Addresses the Full Range of Psychopathology of Adolescent Anorexia Nervosa - Lock, James; Nicholls, Dasha (Frontiers in Psychiatry, 2020)
Family-based Treatment (FBT) for AN is an empirically supported treatment for this disorder. Derived from several different schools of family therapy, it is a highly focused approach that initially targets weight restoration under parental management at home. However, the view that manualized FBT is solely a behavioral therapy directing parents to re-feed their children AN with the single purpose of weight gain is a common but misleading over simplification of the therapy. Indeed, weight restoration is the main goal only in phase 1 of this 3 phase treatment. When practiced with fidelity and skill, FBT’s broadest aim is to promote adolescent development without AN thoughts and behaviors interfering and disrupting these normal processes. Although weight restoration is a key starting point in FBT, the entire course of treatment takes into consideration the ongoing impact of starvation, cognitions, emotions and behaviors on adolescent development. These factors associated with maintaining low weight are viewed in FBT as interfering with the adolescent being able to take up the tasks of adolescence and thus must be overcome before fully turning to those broader adolescent tasks. In addition, FBT recognizes that adolescence takes place in the context of family and community and respects the importance of learning in a home environment both for weight gain as well as related developmental tasks to have a lasting effect. Specifically, in this article we describe how the current FBT manualized approach addresses temperament/personality traits, emotional processing, cognitive content and process, social communication and connections, psychiatric co-morbidity, and family factors. This report makes no claim to superiority of FBT compared to other therapies in addressing these broader concerns nor does it add interventions to augment the current manual to improve FBT.